Effective treatment of logistics resource issues in the Air Force Planning, Programming, and Budgeting System (PPBS) process - Camm, Frank A., 1949-; Lewis, Leslie; Rand eBooks (Santa Monica, CA : RAND, 2003)
The Air Force's logistics supply chain involves the participation of many organizations, inside and outside the Air Force, to serve a variety of users with differing needs. The Air Force uses the Planning, Programming, and Budgeting System (PPBS) to fund all elements of the supply chain at levels that give its users appropriate levels of service. The PPBS process has a great deal of difficulty doing this well. Important changes in the Air Force PPBS, financial management, and logistics management processes over the past 15 years have made the task even more difficult. The authors of this report propose several changes in strategy and policy designed to help the Air Force manage and fund its logistics supply chain in a more integrated manner-a manner that can set goals relevant to its customers and use closed-loop accountability systems to manage the supply chain, end-to-end, against these goals. Full implementation of the changes proposed would challenge Air Force organizational culture. The authors identify specific cultural barriers that the Air Force must address to effectively pursue the changes they propose.
Introduction -- How the PPBS Process Addresses Resource Questions Relevant to DLRs: Policy Issues -- Proposed Changes in Strategy and Policy -- Complementary Initiatives That Could Facilitate Effective Change -- General Organizational Barriers to Effective Change -- Summary.
"Project Air Force."
Includes bibliographical references (p. 103-106).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Appropriations and expenditures; United States. -- Air Force -- Procurement; Logistics -- Management; Military planning -- United States; Program budgeting -- United States; Electronic books